An analytical approach for urban groundwater transit time distributions accounting for the effect of stormwater infiltration system - Jing, Miao; Pujades, Estanislao; Lu, Chunhui (Journal of hydrology (Amsterdam), 2022)
•We developed a novel analytical model for regional groundwater transit time distributions s accounting for the impact of stormwater infiltration systems.•Global sensitivity analysis successfully identifies the most important parameters for urban groundwater TTDs.•The urban groundwater flow regime cannot be fully restored to the pre-urban conditions even with the aid of stormwater infiltration systems. The stormwater infiltration system (SIS) has been recognized as a feasible way to manage stormwater and restore streamflow. As a lumped representation of the flow and transport processes, the groundwater transit time distribution (TTD) is highly relevant to this restoration goal. However, the influence of the SIS on groundwater TTDs has rarely been studied. In this paper, we propose a novel analytical model for groundwater TTDs in regional urban aquifers accounting for the impact of the SIS. This analytical solution is developed for a homogeneous 2-D cross-section of an idealized unconfined aquifer following the Dupuit-Forchheimer assumption. The analytical solution is verified through the comparison with simulated TTDs using the Lagrangian particle tracking algorithm. The global sensitivity analysis reveals that the stormwater infiltration rate, the number of infiltration facilities, the size of the urban area, and the evapotranspiration are the most important factors for groundwater mean transit times (MTTs). Although groundwater discharge and MTT can be restored to the pre-urban one, groundwater TTDs will inevitably deviate from the pre-urban ones due to the alteration from diffuse recharge to infiltration-focused recharge, indicating that the urban groundwater flow regime cannot be fully restored to the pre-urban conditions. Overall, as a first-order approximation of the real-world urban groundwater system, the proposed analytical model provides decision-making support for urban water resources management and the design of the SIS.